Tetragonal distortion induced perpendicular magnetic anisotropy in (Fe0.5Ni0.5)xRh(1_x )alloy thin films - DEĞER, CANER (ELSEVIER, 2021)
We investigated the structural and magnetic properties of (Fe0.5Ni0.5)xRh1_x alloy thin films grown on MgO (100) substrate. The crystal lattice parameters of the alloy are tailored via the tetragonal distortion from the substrate by varying the composition. The change in the lattice parameters and compositions allowed us to control the magnetic properties as well. For thin films with a higher concentration of ferromagnetic content exhibit strong in-plane magnetic anisotropy. Perpendicular magnetic anisotropy (PMA) was observed around 40% of FeNi. We show that the main contribution to the PMA around 40% FeNi is originated from the tetragonal distortion in the crystal, via first-principles calculations.
Keywords: Perpendicular magnetic anisotropy; Ferromagnetic resonance; Crystal structure; Fe-Ni-Rh alloys; TOTAL-ENERGY CALCULATIONS